Donor–σ–Acceptor Motifs: Thermally Activated Delayed Fluorescence Emitters with Dual Upconversion. (23rd November 2017) - Geng, Yan; D'Aleo, Anthony; Inada, Ko; Cui, Lin‐Song; Kim, Jong Uk; Nakanotani, Hajime; Adachi, Chihaya
Abstract: A family of organic emitters with a donor–σ–acceptor (D‐σ‐A) motif is presented. Owing to the weakly coupled D‐σ‐A intramolecular charge‐transfer state, a transition from the localized excited triplet state ( 3 LE) and charge‐transfer triplet state ( 3 CT) to the charge‐transfer singlet state ( 1 CT) occurred with a small activation energy and high photoluminescence quantum efficiency. Two thermally activated delayed fluorescence (TADF) components were identified, one of which has a very short lifetime of 200–400 ns and the other a longer TADF lifetime of the order of microseconds. In particular, the two D‐σ‐A materials presented strong blue emission with TADF properties in toluene. These results will shed light on the molecular design of new TADF emitters with short delayed lifetimes.